Pengaruh Opini Audit, Audit Tenure, Audit Switching Terhadap Audit Delay Pada Perusahaan Batu Bara - Novita, Della; Waradityas, Selvi Agustin; Febrianti, Rindi Antika; Susilo, Dwi Ermayanti (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
Audit delay is the length of time required to complete the audit report which is calculated starting from the closing date of the financial year until the date of issuance of the audited report. The purpose of this research is to find out how the influence of audit opinion, audit tenure, audit switching on audit delay in coal sector companies listed on the Indonesia Stock Exchange (IDX). The factors tested in this study are audit opinion, audit tenure, and audit switching as independent variables and audit delay as the dependent variable. The sample in this study are coal sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period, totaling 16 companies. The analysis technique of this study uses the classical assumption test, multiple linear regression equations, and hypothesis testing with SPSS 26. The results prove that audit opinion has a positive effect on audit delay, audit tenure has a negative effect on audit delay, audit switching has a negative effect on audit delay.